PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KOMITMEN KERJA KARYAWAN MELALUI MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING - Herlangga Nurohman, Dimas (Jurnal Bina Bangsa Ekonomika, 2025)
This study aimed to examine the direct and indirect influence of work discipline & work environment on employee work commitment through work motivation. The sample of this study is the employees of UPTD Puskesmas Cipicung and UPTD Puskesmas Luragung with the totally 80 respondents and used saturated sampling techniques. This study used regression equation path analysis model to examined the inderect influence of work discipline and work environment on employee work commitment through work motivation as a intervening variable with Statistical Program for Social Sciences (SPSS) version 26 as an analysis tools. The research instrument was a physical questionnaire containing statements and distributed directly to respondents. The results of the proposed research conclude that (1) work discipline had a positive and significant effect on employee work commitment. (2) work environment had a positive and significant effect on work commitment. (3) work discipline had a positive and significant effect on work commitment. (4) work environment had a positive and significant effect on work commitment. (5) work motivation had a positive and significant effect on work commitment. (6) work discipiline had no effect and insignificant on employee work commitment through work motivation. (7) work environment had a positive and significant effect on employee work commitment through work motivation.